MEMBENTUK KARAKTER UNGGUL DI SEKOLAH INKLUSIF: STUDI KASUS STRATEGI GURU DI SD PERADABAN CILEGON - Farhurohman, Oman; Mira, Ira; Putri, Yolanda; Robi’atul Adawiyah, Siti (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2023)
This study aims to determine the strategy in combined character education for children with special needs and normal children at Cilegon Civilization Elementary School which includes the cognitive domain or knowledge of morals, the affective domain or moral awareness, and the psychomotor domain or moral action as well as knowing the supporting and inhibiting factors in these character education activities. This study uses qualitative research methods that allow researchers to describe the state of character education in schools. Based on the research findings, it is found that the teacher's strategy in the cognitive domain includes planning through lesson plans that are tailored to the needs, implementation through grouping students based on multiple intelligences, adding shadows for children with special needs, and methods used such as storytelling methods, projects, learning outside the classroom, and linking learning materials with verses of the Koran and hadiths, and evaluation using the 2013 curriculum focuses on character education. While the inhibiting factors are divided into 2, namely internal and external. The internal ones are the heterogeneity of students in one class, and the lack of human resources capable of handling students with severe special needs. The external ones are Judgement from the environment and large operational costs.